THE PERSPEKTIF THEORY OF PLANNED BEHAVIOR TERHADAP INTENSI PNS UNTUK MELAKUKAN WHISTLEBLOWING - Sarwenda Biduri; Wiwit Hariyanto; Eny Maryanti; Nurasik Nurasik; Sartika Sartika (Media Mahardhika, 2022)
This study aims to determine attitudes, subjective norms and control behavior on the intentions of civil servants to carry out whistleblowing: a theoretical perspective on planned behavior (study of the Sidoarjo Regency Government). This study has a sample of civil servants (PNS) who have been in accordance with predetermined criteria. The sample of this research is 78 employees. Meanwhile, the analytical tool used is the questionnaire tabulation, data collection in the form of test validity and reliability testing. The data in this study were processed using SPSS version 18.0. The results of the validity and reliability tests for each indicator on the independent variables show > 0.3 and have Cronbach's Alpha > 0.06 so that the data can be said to be valid and reliable. In this study using data analysis tools in the form of multiple regression. Meanwhile, in the t-test, attitude as (X1) has a sig value of 0.237, subjective norm as (X2) has a sig 0.045, controlling behavior as (X3) has a sig value of 0.000. According to the research results, it can be concluded that subjective norms and control behavior affect the intention to do whistleblowing. But attitude does not affect the intention to do whistleblowing.